Hierarchical multi-level block copolymer patterns by multiple self-assembly. Issue 17 (15th April 2019) - Jung, Hyunsung; Shin, Won Ho; Park, Tae Wan; Choi, Young Joong; Yoon, Young Joon; Park, Sung Heum; Lim, Jae-Hong; Kwon, Jung-Dae; Lee, Jung Woo; Kwon, Se-Hun; Seong, Gi Hun; Kim, Kwang Ho; et al.
Abstract : Unusual pattern generation of various 2D and 3D nanostructures can be achieved by the multiple self-assembly of block copolymers (BCPs) such as big-dot, double-dot, line-on-dot, pondering, dot-in-honeycomb, dot-in-pondering, and line-on-pondering patterns. Abstract : Uniform, well-ordered sub-20 nm patterns can be generated by the templated self-assembly of block copolymers (BCPs) with a high Flory–Huggins interaction parameter ( χ ). However, the self-assembled BCP monolayers remain limited in the possible structural geometries. Here, we introduce a multiple self-assembly method which uses di-BCPs to produce diverse morphologies, such as dot, dot-in-honeycomb, line-on-dot, double-dot, pondering, dot-in-pondering, and line-on-pondering patterns. To improve the diversity of BCP morphological structures, we employed sphere-forming and cylinder-forming poly(styrene- block -dimethylsiloxane) (PS- b -PDMS) BCPs with a high χ . The self-assembled mono-layer and double-layer SiO x dot patterns were modified at a high temperature (∼800 °C), showing hexagonally arranged (dot) and double-hexagonally arranged (pondering) SiO x patterns, respectively. We successfully obtained additional new nanostructures (big-dot, dot-in-honeycomb, line-on-dot, pondering, dot-in-pondering, and line-on-pondering types) through a second self-assembly of cylinder-forming BCPs using the dot and pondering patterns as guiding templates. This simple approach can likely be extended to the multiple self-assembly of many other BCPs with good functionality, significantly contributing to the development of various nanodevices.